Gaya Hidup Elit di Kota, Sederhana di Desa: Ditengah Lemahnya Kondisi Ekonomi Mahasiswa Rantau di Kota Kupang - Rosary, Yulia Oktaviana; Jaimun, Elfrida Trivonia; Seran, Maria Bernadette Esi; Lian, Yohanes Pemandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
ABSTRACT The lifestyle phenomenon of out-of-town students in Kupang City shows a significant shift in behavior, where they tend to adopt an elite lifestyle despite economic limitations. This study aims to identify factors that influence students’ consumptive lifestyles, as well as their impact on their mental well-being. Using a qualitative approach through in-depth interviews, this study revealed that social pressure, the influence of social media, and the desire to be accepted in the social environment play a major role in shaping consumptive behavior. Out-of-town students often feel alienated and try hard to adjust to social norms that prioritize appearance. The results of the study indicate the need for stronger social support for out-of-town students to help them balance social aspirations with the economic realities they face, as well as the importance of education about financial management to prevent excessive consumptive behavior.